(untitled) (Foro de Educacion, 2018)
The question of the transmission of a language, from an integral perspective, requires categories in a wider sense than merely the linguistic one, since it implies incorporating the language and its context as applied linguistics (intercultural pragmatics, intercultural communication and intercultural learning) and sees the anthropological point of view of teaching as a socio-historical process. This intercultural orientation integrating language and its context contrasts in recent years with a more instrumentalist demand for language learning. In this tension, between a more instrumentalist demand and a humanistic dimension of the process, I center my research, from an interdisciplinary perspective and in teaching-learning from an intercultural perspective. The possibilities that this approach shows us have led me to reflect on the space that opens us the incorporation of a language understood as the contact with other identities and to incorporate multiple identities. This leads us to the need to investigate and reflect the principles of the communicative method, the intercultural principles and finally the principles of an ethical behavior. Several texts of Kant, both critical and postcritical, have helped us to show that the methodological principles of language transmission or intercultural mediation are crucial to learning a language. Such theoretical-empirical foundations that support these principles also help to find new proposals within the communicative method. The theoretical reflection is accompanied by different examples and practical proposals.